Evidence from APOGEE for the presence of a major building block of the halo buried in the inner Galaxy. Issue 1 (20th November 2020) - Horta, Danny; Schiavon, Ricardo P; Mackereth, J Ted; Pfeffer, Joel; Mason, Andrew C; Kisku, Shobhit; Fragkoudi, Francesca; Allende Prieto, Carlos; Cunha, Katia; Hasselquist, Sten; Holtzman, Jon; Majewski, Steven R; et al.
ABSTRACT: We report evidence from APOGEE for the presence of a new metal-poor stellar structure located within ∼4 kpc of the Galactic Centre. Characterized by a chemical composition resembling those of low-mass satellites of the Milky Way, this new inner Galaxy structure (IGS) seems to be chemically and dynamically detached from more metal-rich populations in the inner Galaxy. We conjecture that this structure is associated with an accretion event that likely occurred in the early life of the Milky Way. Comparing the mean elemental abundances of this structure with predictions from cosmological numerical simulations, we estimate that the progenitor system had a stellar mass of ∼5 × 10 8  M⊙, or approximately twice the mass of the recently discovered Gaia-Enceladus/Sausage system. We find that the accreted: in situ ratio within our metal-poor ([Fe/H] < –0.8) bulge sample is somewhere between 1:3 and 1:2, confirming predictions of cosmological numerical simulations by various groups.